Expression Pattern of the Aspartyl-tRNA Synthetase DARS in the Human Brain - Fröhlich, Dominik; Suchowerska, Alexandra K.; Voss, Carola; He, Ruojie; Wolvetang, Ernst; von Jonquieres, Georg; Simons, Cas; Fath, Thomas; Housley, Gary D.; Klugmann, Matthias (Frontiers in Molecular Neuroscience, 2018)
Translation of mRNA into protein is an evolutionary conserved, fundamental process of life. A prerequisite for translation is the accurate charging of tRNAs with their cognate amino acids, a reaction catalyzed by specific aminoacyl-tRNA synthetases. One of these enzymes is the aspartyl-tRNA synthetase DARS, which pairs aspartate with its corresponding tRNA. Missense mutations of the gene encoding DARS result in the leukodystrophy Hypomyelination with Brain stem and Spinal cord involvement and Leg spasticity (HBSL) with a distinct pattern of hypomyelination, motor abnormalities, and cognitive impairment. A thorough understanding of the DARS expression domains in the central nervous system is essential for the development of targeted therapies to treat HBSL. Here, we analyzed endogenous DARS expression on the mRNA and protein level in different brain regions and cell types of human post mortem brain tissue as well as in human stem cell derived neurons, oligodendrocytes, and astrocytes. DARS expression is significantly enriched in the cerebellum, a region affected in HBSL patients and important for motor control. Although obligatorily expressed in all cells, DARS shows a distinct expression pattern with enrichment in neurons but only low abundance in oligodendrocytes, astrocytes, and microglia. Our results reveal little homogeneity across the different cell types, largely matching previously published data in the murine brain. This human gene expression study will significantly contribute to the understanding of DARS gene function and HBSL pathology and will be instrumental for future development of animal models and targeted therapies. In particular, we anticipate high benefit from a gene replacement approach in neurons of HBSL mouse models, given the abundant endogenous DARS expression in this lineage cell.